Vaccine package inserts and prescribing habits of obstetricians-gynecologists for maternal vaccination. Issue 10 (3rd October 2021) - Saini, Jannat; Ellingson, Mallory K.; Beigi, Richard H.; MacDonald, Noni E.; Top, Karina A.; Carroll, Sarah; Omer, Saad B.
ABSTRACT: Despite ample evidence of the safety and efficacy of the influenza vaccine and the tetanus, diphtheria, and acellular pertussis (Tdap) vaccine during pregnancy, two-thirds of pregnant women do not receive these vaccines. Providers have a significant role in increasing prenatal vaccine uptake. It is important to understand how different sources of vaccine prescribing information, such as Food and Drug Administration package inserts, influence provider recommendations. We aimed to examine the role of vaccine package inserts in provider recommendations and perceptions of safety and effectiveness of vaccines during pregnancy. A cross-sectional survey was mailed to a random, weighted sample of American College of Obstetricians and Gynecologists Fellows living in the United States in March 2019. Providers were asked about their attitudes toward package inserts, and to evaluate sample package insert statements following two different labeling rules. Their evaluations of each rule were then compared. Of the 321 respondents, the majority (90%, 288/321) recommended and/or administered maternal vaccinations. Few respondents (7.8%, 25/321) read package inserts for information regarding vaccination. Respondents were less likely to recommend sample vaccines with Pregnancy and Lactation Labeling Rule-complying inserts (46.1%, 148/321) than vaccines with Pregnancy Category inserts (87.5%, 282/321). Although most providers did not actively utilize vaccine package inserts to inform recommendations, the previous Pregnancy Categories rule was preferred compared to the Pregnancy and Lactation Labeling Rule. Collaborative efforts to update inserts with current clinical practices for pregnancy would be valuable in reducing apprehensiveness around package inserts to generate safer and more cogent recommendations for pregnant women.